1967
DOI: 10.1182/blood.v29.2.242.242
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Splenic X-Irradiation on the Ferrokinetics of Chronic Leukemia with a Clinical Study

Abstract: The usefulness of splenic x-irradiation in the palliative treatment of chronic leukemia is illustrated by the results obtained in the treatment of 18 patients. This form of therapy was generally followed by reduction in organ size, improvement in blood levels, and control of associated anemia. Abnormalities of iron kinetics were defined in nearly all patients prior to therapy. A second ferrokinetic study was performed after remissions were induced by splenic irradiation. In the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This would imply that the cause of anaemia in CLL is not only depressed red cell production because of marrow involvement with malignant lymphocytes, but also increased haemolysis and/or splenic sequestration of red cells. Some ferrokinetic studies indicate that this might be the case (Awwad et al, 1967), but this remains to be demonstrated in a large series of patients.…”
Section: Discussionmentioning
confidence: 93%
“…This would imply that the cause of anaemia in CLL is not only depressed red cell production because of marrow involvement with malignant lymphocytes, but also increased haemolysis and/or splenic sequestration of red cells. Some ferrokinetic studies indicate that this might be the case (Awwad et al, 1967), but this remains to be demonstrated in a large series of patients.…”
Section: Discussionmentioning
confidence: 93%